A Case of Comparative Study of Loan Performance in Selected Indian Private Banks: An Important Tool of Profitability - Vohra, P. S.; Sehgal, Preeti (Indian Journal of Finance, 2012)
The banking sector is the wheel of any economy. This sector is the most dominant sector of the financial system in India, with good valuations and increasing profits. After liberalization in 1991, the banking industry underwent major changes. Private Banks came into force, and now, they are playing a major role in the development of the Indian banking industry. In the process, they have jolted the public sector banks out of complacency and have forced them to become more competitive. The objective of present paper is to analyze the major component of the lending policy of the Indian private sector banks. This attempt also sheds light on a comparative study of financial performance between few selected private banks through their different lending options. In this attempt, the authors have just tried to emphasize the role of loan performance as a key agent in the profitability of private banks during the years 2002 - 2007.